Nursing care models - T. Szewczyk, Maria; Cierzniakowska, Katarzyna; Ślusarz, Robert; Cwajda, Justyna; Stodolska, Alina (Przewodnik Lekarza/Guide for GPs, 2005)
International nursing care includes more than 20 models. They are divided on four categories: environmental, self-care and needs deficit, needs, system and cooperation. In surgery nursing main practical models are: Virginia Henderson model – needs category, sister Calista Roy model – system and cooperation and Dorothy Orem model – self-care and needs deficit model.